2018
DOI: 10.30867/action.v3i2.95
|View full text |Cite
|
Sign up to set email alerts
|

Pemberian MP-ASI dini dengan status gizi (PB/U) usia 4-7 bulan di Kecamatan Ratu Samban Kota Bengkulu

Abstract: Infants who fail to grow much occur in the third month or fourth month of early life. Early breastfeeding of the ASI causes mothers not to give breast milk and cause infectious diseases that result in stunting in infants. The purpose of this research is to find out the relationship of early breastfeeding with nutritional status (PB/U) age 4-7 months in Ratu Samban Sub-district of Bengkulu City.  This research uses analytic observational with a cross-sectional design. The results showed the nutritional status o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 7 publications
1
8
0
7
Order By: Relevance
“…Stunting merupakan gangguan gizi kronis yang menyebabkan pertumbuhan tinggi anak tidak sesuai dengan bertambahnya umur balita (Sariy et al, 2018). Stunting dikenal dengan istilah pendek dan sangat pendek.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Stunting merupakan gangguan gizi kronis yang menyebabkan pertumbuhan tinggi anak tidak sesuai dengan bertambahnya umur balita (Sariy et al, 2018). Stunting dikenal dengan istilah pendek dan sangat pendek.…”
Section: Pendahuluanunclassified
“…Beberapa faktor diketahui sebagai faktor resiko terjadinya stunting. Penyakit infeksi, inisiasi menyusui dini, pemberian ASI esklusif dan riwayat berat badan lahir rendah merupakan faktor-faktor yang mempengaruhi terjadinya stunting (Sariy et al, 2018;AL Rahmad & Miko, 2016). Selain itu, Riwayat pemberian ASI eksklusif dan waktu pemberian makanan pendamping ASI yang tepat, dapat mencegah stunting (Sariy et al, 2018).…”
Section: Pendahuluanunclassified
“…Hal ini disebabkan karena sistem pencernaan yang belum siap untuk memproses makanan semi-padat dan makanan padat. Oleh karenanya, anak yang diberikan MP-ASI terlalu dini akan beresiko menderita diare dan infeksi saluran pernapasan atas (Beka Sariy, Yosephin Simanjuntak, & Suryani, 2018).…”
Section: Jurnal Kesehatan Manarangunclassified
“…In 2009 in 4 districts in West Java Province, it was found that the implementation of exclusive breastfeeding had failed since the first three days of birth, namely more than 80 percent of respondents who were not exclusively breastfed for four months had given prelacteal food/drinks in the first three days to their babies. Formula feeding as prelactal is often done in PMB, Maternity Clinic and Hospital with the main reasons because breast milk has not come out, the baby still has difficulty suckling, anatomical abnormalities of the breast and the mother's condition is weak (Sariy, Simanjuntak, & Suryani, 2018).…”
Section: Introductionmentioning
confidence: 99%